Disintermediation and tourism industry: a study of travel agent survivality / Nik Alif Amri Nik Hashim - Nik Hashim, Nik Alif Amri (2013)
Tourism business has changed due to the usage of internet as it offers a new distribution channel whereby numerous people are doing their transaction through online and they have become passionate to this activity. New technologies have help the online user to access rapid internet connection, make secure transactions, and provide easier and fast services which can be the causes of disintermediation in tourism industry. This is due to the fact that technology has allowed the travel consumer to communicate and contact directly with the suppliers. Seeing disintermediation as the main issue and problem here, this paper aim to investigate the travel agencies direct impact on disintermediation and strategies used by travel agencies in maintaining their business if they have been excluded by the tourism suppliers in Malaysia. A qualitative approach through face to face interview with managers of travel agent is considered to be the most suitable method for investigating this issue. The result revealed that, disintermediation has given positive and negative impact to travel agent. Travel agent need to take the threat of disintermediation as their opportunity to build up their business. The finding also shows that every travel agencies have their own strategies in facing disintermediation. However, the implementation of website and e-commerce practices is the most useful strategy for travel agents to survive in future business.